Characterization of the complete mitochondrial genome of Wuhaniligobius polylepis (Gobiiformes: Gobiidae) and phylogenetic studies of Gobiiformes - Li Gong; Bingjian Liu; Zhen-Ming Lü; Li-Qin Liu (Mitochondrial DNA. Part B. Resources, 2018)
The environmental changes mainly caused by water pollution and human activities have dramatically threatened the survival of the small-scaled Wu’s goby W. polylepis. In the present study, the complete mitogenome of Wuhaniligobius polylepis was determined, which is 16,496 bp in length, containing 13 PCGs, two rRNA genes, 22 tRNA genes and a putative control region. The overall base composition is 28.6%, 29.0%, 26.7%, and 15.7% for A, T, C and G, respectively. The 13 PCGs encode 3,802 amino acids in total, twelve of which use the initiation codon ATG except COI, which uses GTG. In order to explore the systematic status of W. polylepis and further phylogenetic study of Gobiiformes, a maximum-likelihood tree was constructed based on the concatenated sequences of 12 PCGs. The result showed that Pseudogobius, Hemigobius, and Mugilogobius clustered into a clade and then formed a sister-group with W. polylepis, suggesting the invalid former name of M. polylepis or E. polylepis.